How did Swiss forest trees respond to the hot summer 2015? - Burri, Susanne; Haeler, Elena; Eugster, Werner; Haeni, Matthias; Etzold, Sophia; Walthert, Lorenz; Braun, Sabine; Zweifel, Roman (DIE ERDE – Journal of the Geographical Society of Berlin, 2019)
Central Europe experienced an exceptionally hot summer in 2015. The area of investigation in the Central Alps in Switzerland faced the second warmest summer since the beginning of measurements in 1864. As a consequence, agriculture suffered from considerable production losses. But how were forests affected by the hot summer? We analyzed stem growth data, measured by automated point dendrometers, from 50 trees across nine sites covering the four main Swiss tree species spruce (Picea abies), fir (Abies alba), beech (Fagus sylvatica) and oak (Quercus spp.) in the years 2014 (relatively wet and cool) and 2015 (hot and dry). Annual growth and environmental conditions were determined by, and related to, the growing period based on daily resolved growth data. Our multi-species approach revealed a wide range of responses. Radial growth of spruce was largely reduced during the hot summer 2015 for sites located below 1500 m a.s.l.. Growth of beech responded even positively at several sites on the Swiss Plateau. Fir and oak did not significantly deviate from their respective average growth rate. We conclude that one hot summer actually matters for stem growth, but its effect is not a priori negative. The timing of the heat wave is of highest importance. A relatively wet previous year, a wet spring and the relatively late occurrence of the heat wave in the wood growth period led to a less strong growth reduction than what could have been expected from agricultural plants. Endogenous effects like mast fruiting and legacy effects from past conditions are suggested to further play an important role for stem growth.